Innovation in the European chemical industry - Horst Albach; David B. Audretsch; Manfred Fleischer; Robert Greb; Evelyn Höfs; Lars-Hendrik Röller; Ines Schulz (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
Firms in the European chemical industry have been among the most successful firms world wide. However, they have had to undertake severe restucturing in order to maintain their market position. These efforts focused in particular on strengthening their innovative capability as product and process innovation have become the most decisive factors in global competition. In order to improve the innovative conditions, the European Commission has supported the Community Innovation Survey (CIS). 1992/1993 was the first time that large-scale harmonised innovation surveys were carried out in all Member States of the European Union. This study uses the CIS micro data from nearly 2000 European chemical firms. This study focuses on the identification of innovative trends within the chemical industry between 1984 and 1993. Using data from annual reports of nine selected European stock companies, the study identifies those areas of the chemical industry currently having the highest innovative potential. Three speciality categories are identified as having the highest number of innovations during this ten year period: chemicals, paints/varnishes, and plastics. – – Obwohl viele europäische Unternehmen der chemischen Industrie in den vergangenen Jahrzehnten zu den erfolgreichsten in der Welt zählten, mußten sie sich Anfang der neunziger Jahre einem gravierenden Strukturwandel unterziehen, um ihre Position behaupten zu können. Die Fähigkeit der Unternehmen, Innovationen hervorzubringen, stand und steht dabei im Mittelpunkt. Mit dem Ziel, die Rahmenbedingungen für Innovationen zu verbessern, führte die EU-Kommission 1993 eine europaweite Innovationserhebung, den Community Innovation Survey (CIS) durch. In dieser Studie wurden die anonymisierten Antworten von nahezu 2000 Unternehmen der chemischen Industrie analysiert. Um Innovationstrends aufzuzeigen zu können, wurden darüber hinaus Geschäftsberichte von neun großen europäischen Chemieunternehmen ausgewertet. So wurden die Sparten Spezialitäten, Farben/Lacke und Kunststoffe als diejenigen Sparten identifiziert, die im Untersuchungszeitraum (1984-1993) die meisten Innovationen aufwiesen.
Keywords: 330